2012
DOI: 10.1186/1471-244x-12-159
|View full text |Cite
|
Sign up to set email alerts
|

Insight, psychopathology, explanatory models and outcome of schizophrenia in India: a prospective 5-year cohort study

Abstract: BackgroundThe sole focus of models of insight on bio-medical perspectives to the complete exclusion of local, non-medical and cultural constructs mandates review. This study attempted to investigate the impact of insight, psychopathology, explanatory models of illness on outcome of first episode schizophrenia.MethodPatients diagnosed to have DSM IV schizophrenia (n = 131) were assessed prospectively for insight, psychopathology, explanatory models of illness at baseline, 6, 12 and 60 months using standard inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
135
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(145 citation statements)
references
References 45 publications
5
135
3
2
Order By: Relevance
“…Similar age range has been reported in this environment [29,30], however, reported data on age are usually interpreted cautiously considering the widespread of illiteracy among majority of patients and their caregivers in this setting. In contrast to findings of some other studies [26,27,29], preponderance of females was noted in this study. However, Yusuf et al [31] reported a preponderance of female patients.…”
Section: Socio-demographic Profilecontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar age range has been reported in this environment [29,30], however, reported data on age are usually interpreted cautiously considering the widespread of illiteracy among majority of patients and their caregivers in this setting. In contrast to findings of some other studies [26,27,29], preponderance of females was noted in this study. However, Yusuf et al [31] reported a preponderance of female patients.…”
Section: Socio-demographic Profilecontrasting
confidence: 99%
“…In this study, majority of the subjects were young and the illness also began at a relatively young age. This is consistent with the findings in previous studies [26,27] and confirms the fact that schizophrenia usually begins at an early age [28]. Similar age range has been reported in this environment [29,30], however, reported data on age are usually interpreted cautiously considering the widespread of illiteracy among majority of patients and their caregivers in this setting.…”
Section: Socio-demographic Profilesupporting
confidence: 92%
“…Many reports, which have systematically elicited EMs, have documented the presence of multiple and contradictory beliefs about illness across cultures (Kapoor, 1975;Gater et al, 1991;Lloyd et al, 1998;Joel et al, 2003;McCabe and Priebe, 2004;Saravanan et al, 2007aSaravanan et al, ,b, 2010Johnson et al, 2012Johnson et al, , 2013Johnson et al, , 2014. EMs are usually a conglomeration of emic and etic approaches involving ethnocultural, personal and idiosyncratic beliefs and components from both within and outside culture.…”
Section: Single and Multiple Explanatory Modelsmentioning
confidence: 97%
“…Pluralistic societies employ multiple approaches to health and illness (Jacob, 1999). The fact that people with non-medical beliefs regularly take psychotropic medication (Saravanan et al, 2007a(Saravanan et al, ,b, 2010Johnson et al, 2012Johnson et al, , 2013Johnson et al, , 2014 argues for the complexity of the response to chronic and disabling illness. Research has documented a complex list of reasons and circumstances, which facilitate medication compliance and which are not necessarily voluntary or rational (Tranulis et al, 2011).…”
Section: Single and Multiple Explanatory Modelsmentioning
confidence: 99%
“…In a 10-year longitudinal follow-up study, Shrivastava et al (2010) showed that compared to non-recovered group, mean duration of untreated psychosis was longer for a group, which showed clinical recovery as assessed on the Clinical Global Impression Scale. A recent study evaluated the predictors of 5-year outcome of patients with schizophrenia and reported that level of insight, number of non-medical explanatory models and individual explanatory models held during the later course of the illness have a significant impact on the outcome (Johnson et al 2012).…”
Section: Course and Outcomementioning
confidence: 99%